Structure and Dynamics of Zr4+ in Aqueous Solution: An Ab Initio QM/MM Molecular Dynamics Study - Suwardi Suwardi; Harno Dwi Pranowo; Ria Armunanto (Universitas Gadjah Mada, 2015)
A QM/MM molecular dynamics (MD) simulation has been carried out using three-body corrected pair potential to investigate the structural and dynamical properties of Zr4+ in dilute aqueous solution. Structural data in the form of radial distribution function, coordination number distribution, and angular distribution function were obtained. The results indicate eight water molecules coordinate to zirconium ion and have two angles of O-Zr4+-O, i.e. 72.0° and 140.0° with a Zr4+-O distance of 2.34 Å. According to these results, the hydration structure of Zr4+ ion in water was more or less well-defined square antiprismatic geometry. The dynamical properties have been characterized by the ligand’s mean residence time (MRT) and Zr4+-O stretching frequencies. The inclusion of the three-body correction was important for the description of the hydrated Zr4+ ion, and the results indicated in good agreement with experimental values.